Opinion of the junior doctors on the existing morale, support and autonomy at their workplace and the factors positively influencing them (BIRDEM Medical Journal, 2021)
Background: Junior doctors form the majority of the workforce in patient care. Their job is perilous, highly critical, tedious and exhausting and it is imperative that they stay motivated while at work. Improving the morale of physicians has the potential to increase efficiency, ensure patient safety and improve patient outcomes. We aimed to identify the existing status and explore the factors affecting junior doctors’ morale, their sense of feeling supported and their levels of autonomy in 2 large teaching hospitals in Bangladesh.Methods: This cross-sectional observational study was done across 2 large tertiary hospitals- Bangladesh Institute of Research and Rehabilitation in Diabetes, Endocrine and Metabolic Disorders(BIRDEM) General Hospital and Dhaka Shishu Hospital, over 4 months period from September- December 2020. The study was carried out on 120 junior doctors by an online questionnaire, distributed through emails and Facebook messenger, asking junior doctors to rate their morale, sense of feeling supported and autonomy and rank the top factors that positively affected them.Results: Data were finally collected from 117 junior doctors after 3 incomplete data were discarded. Most of the junior doctors felt ‘neither good nor bad’ in the domains of existing ‘morale’ (44.4%), ‘feeling supported’ (46.5%) and ‘autonomy’ (48.7%). Additionally, ‘good’ morale was seen in 39.3%, while around 34% rated their support system as ‘good’ and around 24% reported a ‘good’ autonomy. The most important factor positively affecting morale was recognition and reward for good performance (70.1%), factor influencing support was an easy access to senior clinicians (70.4%) and that defining autonomy was constant senior supervision of the everyday work (61.1%).Conclusion: The study aims to identify the existing level of morale, support and autonomy of the junior doctors at their workplace and explore the factors positively affecting them. It is concluded from this study that the junior doctors rated their existing morale, support and autonomy as ‘average’. According to the opinions of the doctors, this study also concludes that, to improve their morale, there is a need to recognize and reward their good work and provide positive feedback. Doctors identified an easy access to senior clinicians with a problem was the primary factor influencing support. Finally, junior doctors wanted constant senior supervision of their everyday work in the wards to improve output.BIRDEM Med J 2022; 12(1): 30-35